2006
DOI: 10.1889/1.2433549
|View full text |Cite
|
Sign up to set email alerts
|

P-82: New Design for a Highly Collimating Turning Film

Abstract: We have investigated a new design for a turning film used in combination with wedge‐shaped light guide plates. The selected design has a top periodic lenticular structure that is in registration with the bottom periodic prisms. Relative registration shift in the prisms and the top lenticular structure was found to be beneficial. Use of such turning film drastically enhances the on‐axis brightness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In spite that LEDs are widely used as the light source for backlight in LCDs, the conventional LED of Lambertian angular distribution is not suitable for narrow viewing angle backlight design with eco-display [7][8][9]. Thus, the collimated point light source becomes a good candidate for the direction-dependent-displays.…”
Section: Design Principlementioning
confidence: 99%
“…In spite that LEDs are widely used as the light source for backlight in LCDs, the conventional LED of Lambertian angular distribution is not suitable for narrow viewing angle backlight design with eco-display [7][8][9]. Thus, the collimated point light source becomes a good candidate for the direction-dependent-displays.…”
Section: Design Principlementioning
confidence: 99%
“…It is clearly indicated that the conventional LED with Lambertian angular distribution is not suitable for collimated backlight design [5][6][7]. Therefore, we designed a collimated light source including an LED chip and a parabolic reflector immerged in a high index material, as shown in Figure 2.…”
Section: Collimated Light Sourcementioning
confidence: 99%
“…Recent years, IBM used multi-index material to control the light angular distribution of entering the microstructures [1][2][3][4]. Kodak used a dual-turning film to collimate the light [5]. K.K designed a monolithic block-wise functional light guide and combined with an inverted prism to get the collimated backlight [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Many improved turning films [1,2,3] have been proposed to enhance light utilization efficiency and luminance. One example [1] is shown in Figure 2A.…”
Section: Figure 1 a Conventional Turning Filmmentioning
confidence: 99%